(untitled) (Bangladesh Journal of Neuroscience, 2014)
Background: Stroke is an important cause of death and disability. Prevalence of stroke in Bangladesh differs with age. The risk factors in young differ in comparison to old age group. In this study risk factors of stroke in young in comparison to old age group were evaluated. Objectives: To compare the risk factors associated with stroke in young adult and to those of old age group. Methodology: This comparative study conducted in the department of Medicine and Neurology, Sir Salimullah Medical College & Mitford Hospital, Dhaka from January 2008 to June 2009. One hundred two stroke patient of above 15 years of age were confirmed by CT scan or MRI of brain those were included in young and old age groups. The risk factors of stroke were defined in terms of hypertension, diabetes mellitus, dyslipidaemia, ischemic heart diseases, valvular heart disease, history of transient ischemic attack or stroke, smoking and oral contraceptive pill. Results: Of total 102 cases 17 were young adults and 85 old patients between 19 to 100 years. Mean age young adult was 39.76 (± 6.379) and old age was 65.06 (± 11.238). 61.7% were male & 38.2% were female and the ratio was 1.6:1. Amongst male 58.8% patients were smoker in each age group and only 2.9% old patients were alcoholic. Only 17.6% had previous history of transient ischemic attack or stroke in each age group. 58.8% of young and 48.2% of old were hypertensive. 7% old patients had history of ischemic heart disease. 5.9% of young and 2.4% of old patients had valvular heart disease but no patient had vasculitis. 16.7% old patients had diabetes mellitus. 4.9% of total patients (young 11.8% and 3.5% old) were oral contraceptive pill user. Out of all patients 24.7% old patients and 5.9% young adult was dyslipidaemic. Among all patients 66.7% patients had the Ischemic stroke and 33.3% patients had the hemorrhagic stroke. 68.2% old patients and 58.8% young patients had Ischemic stroke; 31.8% old patients and 41.2% young patients had hemorrhagic stroke. Conclusion: In young age group smoking, transient ischemic attack or stroke, hypertension, valvular heart disease, oral contraceptive pill and in old age group smoking, transient ischemic attack or stroke, hypertension, Ischemic heart disease, diabetes mellitus and dyslipidaemia were found significant risk factors for development of stroke. So modification of risk factors may reduce the incidence of stroke. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 94-100 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17576